State, Civil Society, and Women’s Labour Use in the Millet Ecosystem: Gender Transformative or Exploitative? - Bedamatta, Rajshree; Talukdar, Tulika Rani (Indian Institute of Technology, 2023)
India’s National Food Security Mission, guided by the National Food Security Act, initiated a submission on nutri-cereals focusing on millet crops. In the wake of contestations surrounding different frames of food security and food sovereignty, millet has emerged as a critisector pcal link between women’s labor and local food systems. In Nagaland, the North East Network is leading the revival of millet crops involving local communities, particularly women. In Odisha, a state-supported mission, the Odisha Millet Mission is creating new markets through an institutional process. In both these states, women are at the core of the process as producers and processors. We studied the millet ecosystem in Nagaland (Phek District) and Odisha (Koraput District) to understand the successes, constraints and challenges within this dynamic milieu of increased state and civil society attention to millet. We analyse whether such interventions have transformed women’s lives or relegated them to the background as disempowered and voiceless producers. We used a qualitative research framework comprising 25 in-depth interviews, 25 FGDs and 21 key informant interviews among women farmers, self-help groups (SHGs), and other actors leading the millet programs in both states. In Nagaland, women’s bargaining power within a household has sway over the family’s decision to cultivate millet. In Odisha, the state has directly intervened through an institutional process to intensify the process of women’s participation in millet production and processing. However, the drudgery of work is disproportionately shouldered by women without commensurate financial gains.